VALPROIC ACID IMPROVES NERVE INJURY IN YOUNG RATS WITH EPILEPSY BY REGULATING STXBP1 - Suo guihai; Wang xiaolin; Dai yufei; Wu youjia; Li haiying; Zheng yuqin (Journal of Animal and Plant Sciences, 2025)
This study aims to discuss how valproic acid improves nerve injury in young rats with epilepsy by regulating STXBP1. It also seeks to identify risk proteins for epilepsy through bioinformatics analysis. 30 young rats were divided into three groups, namely Normal, Model, and VA. Each group contained 10 rats. Epilepsy models were established in all groups except the control group. After modeling, the valproic acid group was orally administered 1 mg/kg of valproic acid. Cognitive function was assessed using the water maze experiment, while hippocampal tissue morphology was observed through Nissl staining. The neuronal apoptosis rate in hippocampal tissue was detected using the TUNEL method. Immunohistochemical staining was performed to detect the NMDARl-positive cell rate in hippocampal tissue. Meanwhile, immunoblotting was used to measure the expression levels of STXBP1 and SLC2A1p proteins in hippocampal tissue. Bioinformatics analysis identified STXBP1 as a risk protein for epilepsy. Compared to the control group, the platform search time, neuronal apoptosis rate, NMDARl-positive cell rate, number of crossing platforms, and proportion of original platform search time in the model group of young mice decreased on days 1, 2, 3, and 4 (P<0.001). In addition, the levels of STXBP1 and SLC2A1 proteins decreased (P<0.001). In comparison to the model group, platform search time, neuronal apoptosis rate, and NMDAR1-positive cell rate in the valproic acid group of young mice decreased on days 1, 2, 3, and 4. However, the number of crossing platforms and the proportion of original platform search time increased (P<0.001). In addition, the levels of STXBP1 and SLC2A1 proteins significantly increased (P<0.001). In conclusion, valproic acid can significantly improve cognitive function, reduce the expression of NMDAR1, and inhibit neuronal apoptosis in juvenile epileptic rats. The mechanism might be related to its regulation of STXBP1 expression.
Keywords: Epilepsy; Valproic acid; Cognitive function; STXBP1